Implementation of Map Introduction in Learning to Improve Spatial Thinking Understanding in Elementary School Students in Jambeyan Village - Prihadi, Singgih; Rahmat Runjung, Benyamin Ricky; Yuliana, Hesti; Safitri, Kartika Dewi; Saputri, Maharani Bintang; Saharani, Nariswari Putri; Az Zahra, Nazwah Ummu; Inayah, Nurul Fitri; Katamsa, Risam; Astyo Dhanoko, Thorriqul (Edumedia Solution, 2025)
The community in Jambeyan Village faces challenges in improving spatial literacy among elementary school students, which affects their ability to analyze spatial patterns and geographic phenomena. To address this issue, a community engagement program was implemented to introduce map based learning US a means to enhance spatial thinking skills. The program was conducted from March 17 to 19, 2025, at Jambeyan 1 Public Elementary School, Jambeyan 2 Public Elementary School, and Elementary School Country Jambeyan 3, involving 104 students. The Implementation methods included lectures, discussions, and hands-on activities using land use maps of Jambeyan Village. The results showed a significant improvement in students' understanding of spatial relationships, demonstrated by their ability to interpret land use maps and describe spatial patterns in their surroundings. However, challenges such US limited interactive learning media and inadequate internet access were encountered. Despite these obstacles, the initiative successfully increased students' interest in spatial learning and highlighted the effectiveness of visual learning tools in geography education. Future programs should focus on integrating digital mapping technologies to further enhance learning outcomes.